Advanced Biomaterials in Neuroprotection: Innovations and Clinical Applications - Ramakrishna K.; Viswanadh M.K.; Dumala N.; Chakravarth G.; Venkateswarlu K.; Gutti G.; Yadagiri G.; Duguluri S.; Rai S.N. (My University, 2025)
Biomaterials are biodegradable, biocompatible, and bioinert and mimic the extracellular matrix of the cell. This chapter discusses the current challenges in neuroprotective agents and the advantages of various biomaterials and their applications as neuroprotective agents. Natural and synthetic biomaterials mimic the ECM of the brain and aid drug and cell delivery. Biomaterials are widely used as carriers for the delivery of drugs and other biological substances particularly into the brain. Doping of drugs with biomaterials enhanced their bioavailability, permeability, safety, efficacy, and reduced toxicity and exhibited neuroprotection against AD, PD, stroke, SCI, TBI, ALS, etc. This chapter further addresses biomaterials and their loaded drugs-mediated improvement in neuroprotection by modulating oxidative stress, mitochondrial dysfunction, excitotoxicity, inflammation, and apoptosis. Furthermore, challenges in using biomaterials as a carrier for drug and cell delivery are also discussed in the present chapter. In conclusion, to improve the neuroprotective potential of biomaterials, continued multidisciplinary collaboration and translational research efforts are essential. © The Editor(s) (if applicable) and The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2025.